Constraint handling in optimization‐based control of a heat‐up problem using a transformation approach. Issue 1 (December 2014) - Utz, Tilman; Rhein, Sönke; Graichen, Knut
Abstract An approach is presented for optimization‐based control of a class of boundary‐controlled parabolic partial differential equations, which are subject to state and input constraints. In order to avoid the potential numerical complexity of constrained optimization, suitably chosen asymptotic saturation functions are used to reformulate the original problem in new coordinates. The resulting unconstrained problem can then be solved with methods of unconstrained optimization, which is interesting for use in model predictive control schemes. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)